Extracorporeal shockwave therapy for avascular necrosis of femoral head - Wang, Ching-Jen; Cheng, Jai-Hong; Huang, Chung-Cheng; Yip, Han-Kan; Russo, Sergio (International journal of surgery (London, England), 2015)
The etiology of osteonecrosis of the femoral head (ONFH) is multifactorial. Treatment of ONFH is disease stage dependent. For early stages, femoral head preservation procedures are preferred including core decompression, muscle pedicle grafting and de-rotational osteotomy. Core decompression with bone grafting is considered the gold standard. However, the results are inconsistence and unpredictable. An effective non-invasive method of treatment is imperative. Recently, extracorporeal shockwave therapy (ESWT) has shown beneficial effects in ONFH. ESWT improves pain and function of the hip and regression of the ONFH lesion. ESWT is more effective than core decompression with or without bone grafting, cocktail therapy that combined HBO, ESWT and oral alendronate is shown effective for patients with early osteonecrosis. The purpose of the article is to review, update and summarize the clinical treatment of ONFH using shockwave therapy. •ESWT is an effective and non-invasive method in the treatment of ONFH.•ESWT is more effective than core decompression and bone grafting for early ONFH.•Cocktail therapy and ESWT show comparable results in ONFH.•ESWT is equally effective for ONFH in SLE patients.